The Role of External Auditors in Mediating the Relationship Between Internal Audit and Sustainable Procurement - Sopian, Sopian; Yustiana, Syanni; Prabowo, Muhadi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
The vulnerability of state owned enterprise ( BUMN)’s procurement of goods and services from fraud is still high despite of heavy implementation of internal control function. This research aims to examine the influence of the effectiveness of internal audit on the sustainable procurement of goods and services with the role of external auditors as moderating. This research uses a quantitative method with a survey approach to internal auditors and procurement officer within BUMN. The number of participants involved were 130 participants consisting of auditors, managers and procurement experts in BUMN. PLS SEM software was utilized to analyze the survey results. The research finds that the competence and the independence of internal audit and management support with the effectiveness of internal audit as a mediating variable and the role of external auditors as a moderating variables are able to influence the sustainable procurement of goods and services within the BUMN